2019
DOI: 10.1044/2018_ajslp-18-0037
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of the Prevalence of Speech and Motor Speech Disorders in Youth With 22q11.2 Deletion Syndrome

Abstract: Purpose Speech sound disorders and velopharyngeal dysfunction are frequent features of 22q11.2 deletion syndrome (22q). We report the first estimate of the prevalence of motor speech disorders (MSDs) in youth with 22q. Method Seventeen children and adolescents with 22q completed an assessment protocol that included a conversational speech sample. Data reduction included phonetic transcription, perceptual speech ratings, prosody-voice coding, and acousti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 75 publications
1
29
0
Order By: Relevance
“…The research initially used the provisional term Motor Speech Disorder-Not Otherwise Specified as a placeholder classification for this latter putative disorder (Shriberg, 2010a, 2010b; Shriberg et al, 2010a; Shriberg, Potter, & Strand, 2011). Findings from subsequent research with children with idiopathic SD (Shriberg, 2017) and children with SD in the context of complex neurodevelopmental disorders (Baylis & Shriberg, 2018) supported replacing the provisional term with the present term, Speech Motor Delay (SMD). Specifically, perceptual and acoustic analyses reported in Shriberg (2017) indicated that the early speech-prosody-voice phenotypes of children meeting criteria for the placeholder classification Motor Speech Disorder-Not Otherwise Specified is consistent with a delay in neuromotor precision-stability (i.e., the lower tail of speech motor development).…”
Section: Motor Speech Disorders In Childrenmentioning
confidence: 97%
“…The research initially used the provisional term Motor Speech Disorder-Not Otherwise Specified as a placeholder classification for this latter putative disorder (Shriberg, 2010a, 2010b; Shriberg et al, 2010a; Shriberg, Potter, & Strand, 2011). Findings from subsequent research with children with idiopathic SD (Shriberg, 2017) and children with SD in the context of complex neurodevelopmental disorders (Baylis & Shriberg, 2018) supported replacing the provisional term with the present term, Speech Motor Delay (SMD). Specifically, perceptual and acoustic analyses reported in Shriberg (2017) indicated that the early speech-prosody-voice phenotypes of children meeting criteria for the placeholder classification Motor Speech Disorder-Not Otherwise Specified is consistent with a delay in neuromotor precision-stability (i.e., the lower tail of speech motor development).…”
Section: Motor Speech Disorders In Childrenmentioning
confidence: 97%
“…Features of dysarthria and childhood apraxia of speech have been reported in children and in some adults with 22qDS (Kummer et al, 2007;Mills, Gosling, & Sell, 2006;Persson, Laakso, Edwardsson, Lindblom, & Hartelius, 2017;Solot et al, 2001). Speech motor delay has also been described in some children with delay in speech motor development who do not meet criteria for childhood apraxia of speech or dysarthria (Baylis & Shriberg, 2019). See Table 3 for a summary of speech disorders in children with 22qDS.…”
Section: Speech Sound Disordersmentioning
confidence: 99%
“…The Method section and a Supplement for this research series [Supplementary Data] provide detailed information on methods and measures in the finalized version of a classification system termed the Speech Disorders Classification System (SDCS) developed for research in childhood speech sound disorders (Shriberg, Kwiatkowski, & Mabie, 2019). The SDCS, which provides the research framework for the present study, has been used to classify participants’ motor speech status in a number of studies of the genomic and behavioural substrates of persons with speech sound disorders (e.g., Baylis & Shriberg, 2018; Eising et al, 2018; Laffin et al, 2012; Raca et al, 2013; Redle et al, 2015; Rice et al, 2012; Shriberg, Jakielski, & El-Shanti, 2008; Shriberg, Paul, Black, & van Santen, 2011; Shriberg, Potter, & Strand, 2011; Truong et al, 2016; Worthey et al, 2013).…”
Section: Classification Of Motor Speech Disordersmentioning
confidence: 99%